CONTRIBUTION OF INDONESIAN DEMOCRATIC TO ISLAMIC EDUCATION - Erni Haryanti; Firdaus Firdaus (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
This paper aims to show up the reason that Indonesian democratic can give contribution to developing of Islamic education theory, in order to responds of contemporary issues. To achieve of the purpose, this paper was discussing a number of democratic theory and Islamic education contemporary literature with holding a dialogue to Indonesian culture background. Recently, Islamic education theory and practice has undergone some transformations, in its system, curriculum, and institutions. One of the trigger was a demand to implementing a conception of democracy in Islamic education praxis. In Indonesia it was adopted from Pancasila, exactly the Bhineka Tunggal Ika slogan. To realized of that, Indonesian Islamic education institution like madrassa, since 1980s was combined between curriculum Indonesia national and Islamic education. It is be a sign that Indonesian democracy can be an alternative to developing a theory of democratic Islamic education.